2003
DOI: 10.1186/1476-7120-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a wrong diagnosis: false Sinus Venosus Atrial Septal Defect

Abstract: In contrast with transthoracic echocardiography, transesophageal echocardiography provides a sure way to make the diagnosis of sinus venosus atrial septal defect; on the other hand this abnormality is more complex than that seen with the secundum atrial septal defect, and inexperienced operators may fail to recognize properly the defect. In front of a high reported sensitivity using transesophageal echocardiography, specificity is difficult to assess, due to possible underreporting of diagnostic errors. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…Several studies have shown that standard transthoracic echocardiography and most of all, trans‐oesophageal echocardiography shows high sensitivity and specificity in detecting patent foramen ovale, small secundum‐type ASD and also defects of the interatrial foramen primum with the absence of false‐positive results (Shub et al, 1983; Belkin et al., 1994; Schneider et al, 1996). On the other hand, according to human cardiologists, diagnostic errors regarding ASD are more often due to false‐negative results, and this is particularly the case with sinus venosus ASDs (Shub et al, 1983; Pascoe et al, 1996): inexperienced operators may fail to recognize or suspect sinus venosus ASDs when using transthoracic echocardiography and trans‐oesophageal echocardiography, whereas when performed by experienced operators (Gaibazzi et al, 2003), this is the most accurate way to diagnose this complex defect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that standard transthoracic echocardiography and most of all, trans‐oesophageal echocardiography shows high sensitivity and specificity in detecting patent foramen ovale, small secundum‐type ASD and also defects of the interatrial foramen primum with the absence of false‐positive results (Shub et al, 1983; Belkin et al., 1994; Schneider et al, 1996). On the other hand, according to human cardiologists, diagnostic errors regarding ASD are more often due to false‐negative results, and this is particularly the case with sinus venosus ASDs (Shub et al, 1983; Pascoe et al, 1996): inexperienced operators may fail to recognize or suspect sinus venosus ASDs when using transthoracic echocardiography and trans‐oesophageal echocardiography, whereas when performed by experienced operators (Gaibazzi et al, 2003), this is the most accurate way to diagnose this complex defect.…”
Section: Discussionmentioning
confidence: 99%
“…Однако существуют особенности, к которым можно отнести расположение данного дефекта в высоких отделах МПП и недостаточный опыт врача-эхокардиографиста в диагностике редких врожденных пороков сердца у взрослых пациентов. Стандартная бикавальная позиция с одновременной визуализацией обеих полых вен в качестве ориентиров корректной визуализации МПП, используемая для диагностики ООО и наиболее распространенных ДМПП, не оптимальна для визуализации дефектов типа sinus venosus из-за их расположения в высокой части МПП [24]. Эхокардиографист должен иметь особую настороженность в отношении данной патологии, в первую очередь при наличии признаков необъяснимой легочной гипертензии [25,26] З а к л ю ч е н и е Представленный клинический случай иллюстрирует возможность развития ИИ у пациента среднего возраста по механизму парадоксальной эмболии, реализующейся через редкий вариант ДМПП -sinus venosus.…”
Section: с контрастированием а -аксиальный срез: стрелкой указан дмпп по типу Sinus Venosus дефект расположен между левым (лп) и правым пunclassified
“…Precise assessment of the presence and location of the APVDs remains an important prerequisite for planning an adequate surgical approach [6]. Diagnostic difficulties are encountered with transthoracic (TTE) and transesophageal echocardiography (TEE) as well as with the invasive method of oxymetry and selective pulmonary artery angiography [1,[7][8][9][10]. According to previous publications, contrast-enhanced magnetic resonance angiography (MRA) has proven useful because of enabling a 3D reconstruction of the heart and the great vessels for the detection of APVDs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%